Implant‐abutment emergence angle and profile in relation to peri‐implantitis: A systematic review - Sara Soulami; Dagmar E. Slot; Fridus van derWeijden (Wiley, 2022)
Abstract Statement The aim of this systematic review is to analyze literature regarding the relationship between the implant‐abutment emergence angle (EA) and implant emergence profile (EP) and the prevalence of peri‐implantitis. Methods PubMed and the Cochrane Library were searched for studies from initiation up to April 2022. Studies describing the EA and EP in association with peri‐implantitis were considered eligible for this review and selected for inclusion in this review if implant groups with wide and narrow EA and different EP types were described. Results Searches in PubMed and the Cochrane Library led to 1116 unique titles and the inclusion of three studies. These concerned 168-349 implants. Two studies presented the mean prevalence of peri‐implantitis which was 16.7% and 24.8% at the implant level. Both studies showed a significant relationship between peri‐implantitis in bone‐level implant groups with an EA above 30° compared to implants with an EA below 30°. A third study presented marginal bone loss which tended to be smaller when the EA was around 20°-40°. In one of the three included studies, the prevalence of peri‐implantitis was significantly higher if implants had a convex EP compared to a concave or straight EP. Another study showed a significantly higher prevalence of peri‐implantitis in implants with a convex EP compared to other EP types, if combined with an EA above 30°. Conclusions Three eligible studies were found. Reported associations should therefore be considered with caution. Synthesis suggests an association between a larger EA (>30°) and a higher prevalence of peri‐implantitis or marginal bone loss compared to a smaller EA (<30°). A convex EP may also be associated with a higher prevalence of peri‐implantitis. However, causality remains a question.